Model Penilaiann Kinerja Karyawan dengan Personal Balanced Scorecard: (Studi Kasus Universitas Tangerang Raya) - Nur Aziz; Dewanto, Ignatius Joko (MAMEN: Jurnal Manajemen, 2022)
Employee performance is assessed through superiors, subordinates and co-workers. Work performance or employee performance can later be used to determine employee policies in improving their performance in the future. The Personal Balanced Scorecard (PBSC) describes employees in four areas, namely: internal, external, skills and learning, and finance. By applying this method can help the managerial for the purposes of assessing its employees objectively.